Drought Tolerance in Transgenic Potato Cultivar IPB CP1 Expressing MmCuZn-SOD Gene - Musawira; Tjahjoleksono, Aris; Hamim, Hamim; Miftahudin, M. (HAYATI Journal of Biosciences, 2025)
Drought stress induces reactive oxygen species (ROS) accumulation, which is harmful to plant cells. Consequently, it inhibits plant growth and decreases yield. The enzyme superoxide dismutase (SOD), which is encoded by the SOD gene, is the first defence enzyme in the cells that detoxify ROS. The study aimed to analyze the tolerance of transgenic potato cultivar IPB CP1 and its yield under drought-stress conditions. The results showed that transgenic plants had superior morphological characteristics, such as plant height, number of leaves, stem diameter, and plant biomass, than non-transgenic plants. However, photosynthetic rate, chlorophyll content, stomatal conductance, and transpiration rate showed similar levels between the transgenic and non-transgenic plants. The transgenic plants expressing the MmCu/Zn-SOD gene showed lower lipid peroxidation levels than the non-transgenic plants, indicating that the gene works well to reduce the cell's ROS level. Transgenic plant clone CP1S6 showed 13 times higher gene expression and tuber yield than non-transgenic plants. These research indicated that the transgenic plants expressing the MmCu/Zn-SOD gene are more tolerant to drought stress than the non-transgenic plants.